Factors Associated with Stunting among Children Aged 6 – 59 Months Attending Integrated Health Post (Posyandu) in Selapajang and Kedaung Wetan Villages, Neglasari Sub-District, Tangerang City: A Matched Case-Control Study - Solang, Michael Alexander; Trixie, Joue Abraham; Semula, Gloria; Simamora, Tiona; Tanjung, Conny (UI Scholars Hub, 2026)
Stunting is a problem in Indonesia. In 2022, Kedaung Wetan and Selapajang Villages in Neglasari sub-district, Tangerang City, were identified as a priority. This study aimed to identify factors associated with stunting among children (6 – 59 months) in these villages. A matched case-control study consisting of 214 children (107 cases and 107 controls) was conducted, with individual matching based on age, sex, and prematurity at birth. Cases were children with height-for-age (H/A) measurement less than -2SD (according to WHO standard), while controls were children with H/A equal to or greater than -2SD. Conditional logistic regression was used for the multivariable analysis. No statistically significant associations were identified between the factors analyzed and the risk of stunting. However, higher maternal education was associated with higher odds of stunting compared to lower maternal education (OR 4.04, 95% CI 0.96 – 16.95), and among children with low birth weight (LBW) compared to non-LBW (OR 4.02, 95% CI 0.38 – 42.25) Nevertheless, the wide confidence intervals indicate statistical uncertainty. Conversely, lower odds of stunting were found among children not exclusively breastfed compared to those exclusively breastfed (OR 0.39, 95% CI 0.07 – 2.17) and among those with low birth length compared to normal length (OR 0.66, 95% CI 0.43 – 1.01), although none reached statistical significance. The only related variable was clean water (OR 1.06, 95% CI 0.03 – 0.75). In conclusion, several factors were explored as potential determinants, although no statistically associations. Future study procedures should be improved to minimize flaws and improve reliability. Keywords: Birth length, Breastfeeding, Exposure to smoke, Maternal education, Stunting